The in vitro detection of botulinum neurotoxin-cleaved endogenous VAMP is epitope-dependent. (April 2018) - Gray, B.; Cadd, V.; Elliott, M.; Beard, M.
Abstract: The in vitro potency of botulinum neurotoxin (BoNT) serotypes is often measured by monitoring cleavage of their soluble N -ethylmaleimide-sensitive factor attachment protein receptor (SNARE) protein substrates. A frequently used method is Western blot, whereby the full-length protein and cleaved form migrate at different molecular weights. Until now, it has been extremely difficult to detect the cleaved cellular form of the SNARE protein vesicle associated membrane protein 1, 2 or 3 (VAMP1, 2 or 3) by Western blot. These VAMP isoforms are the substrates of BoNT serotypes BoNT/B, D, F and G as well as tetanus neurotoxin. Using custom made anti-VAMP antibodies against epitopes either side of the cleavage sites for BoNT/B, BoNT/D and BoNT/F, we have successfully detected the cleaved C-terminal VAMP fragment in cortical neurons. These new antibodies enable quantitative assessment of the potency of VAMP-cleaving neurotoxins by a gain of signal Western blot assay. Highlights: First report of an antibody that detects botulinum-cleaved VAMP2 in neuron extracts Better accuracy measuring the potency of botulinum B, D, F and tetanus toxin Detection of cleaved VAMP2 by Western blot relies on the antibody epitope location. The cleaved C-terminal VAMP2 fragment is not rapidly degraded within neurons.